The Effect of Rumination and Retrospective Negative Memory on Depression Symptoms of Love Trauma in Young: Positive Strengths as a Moderator - Azadeh Ghahfarokhi , Seyyedeh Monireh; Delmanian, Elaheh; Zarshenas, Helia; Faraji, Asiyeh; Goodarzi, Morteza (International Journal of Education and Cognitive Sciences, 2025)
Introduction:  Most young people will have been exposed to at least one traumatic event in their lifetime. The main aim of this research was to investigate how Positive Strengths can moderate the impact of rumination and negative memories on depression symptoms in young individuals who have experienced love failure. Method: The study employed a cross-sectional design and utilized descriptive-correlational research techniques, as well as structural model and path analysis methods.   The study population included young individuals seeking counseling for emotional issues related to relationships in Tehran between July and October 2023. A sample of 147 individuals was selected using a multi-stage cluster sampling method.   Various instruments, such as Virtues in Action- Inventory of Strengths (VIA-IS), Beck Depression Inventory-II (BDI-II), love Trauma Inventory (LTI), Time Attitude Questionnaire (TAQ), and Rumination scale (RRS) were used for data collection and analysis. Data analysis was conducted using SPSS version 27 for descriptive statistics, Pearson's correlation, SmartPLS version 4, and JAMOVI version 2.4.14 for data analysis and standard coefficients. The significance level was set at 0.05.Results: Based on the findings, the variable of Excellence played a crucial role as a moderating factor in the relationship between the Retrospective negative memory variable and Depression (β= -0.188, P= 0.022), turning this relationship negative. Additionally, the Humanity variable also had a significant impact as a moderating factor in the connection between the Retrospective negative memory variable and Depression (β= -0.127, P= 0.042). Furthermore, the Excellence variable was found to have a significant role as a moderating factor in the relationship between the Rumination variable and Love trauma (β= 0.236, P= 0.025).  Conclusion: the findings suggest that Positive Strengths can help alleviate depression following love trauma in young individuals, while negative memories and rumination can exacerbate depressive symptoms.   Additionally, the moderating effects of transcendence and humanity can mitigate the negative impact of negative memories and rumination, thus reducing the severity of depression.   These findings have implications for the development of treatment programs and psychological interventions aimed at reducing depression in young people who have experienced love failure.